Is there any role of antibiotic as a post procedure prophylaxis in dilatation and curettage? A comparative single centre study at tertiary care centre - Thiyagarajan, Kamalpriya; Chaudhary, Vaishali; Patil, Yogini; Gawali, Vijaykumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Dilatation and curettage (D and C) is one of commonest procedure in the gynaecology. There are still two schools of thoughts pertaining to whether to administer antibiotic as a pre and post procedure prophylaxis or not to administer and hence study planned to evaluate the incidence of infection in patients after dilation and curettage with and without prophylactic antibiotics. Methods: Adults (>18 years) (n=100) who underwent dilatation and curettage procedure for any indication were included and patients with prior history of infection were excluded from the study. Patients were divided into 2 groups; group 1 (n=50) received prophylactic antibiotics and group 2 (n=50) received no prophylactic antibiotics as per the discretion of treating doctor. Results: Infection in both the groups was 2% and there is no statistically significant difference between the groups (p>0.349). Conclusions: Appropriate use of antibiotics can be a cost-effective strategy which can minimize the chances of development of antibiotic resistance and other side effects. Antibiotic are not necessary for pre and post procedure prophylaxis in D and C.